Serratia marcescens outbreak in a neonatal intensive care unit and the potential of whole-genome sequencing. (May 2021) - Muyldermans, A.; Crombé, F.; Bosmans, P.; Cools, F.; Piérard, D.; Wybo, I.
Summary: Background: Serratia marcescens is notorious for its increasing antimicrobial resistance and potential to cause outbreaks in neonatal intensive care units (NICUs). A promising tool in outbreak investigations is whole-genome sequencing (WGS). Objectives: To describe a S. marcescens outbreak (2018–2019) in an NICU and discuss which infection control measures contributed to containment, addressing the potential of WGS. Methods: S. marcescens isolates from patients and the environment isolated during the 2018–2019 NICU outbreak were analysed. In comparison, isolates from previous presumed NICU outbreaks and adult blood cultures were included. WGS and whole-genome multi-locus sequence typing analysis were performed. Results: Sixty-three S. marcescens isolates were analysed. The 2018–2019 outbreak was divided into three clusters, including four environmental strains (drains, N =3; baby scale, N =1). The strains differed significantly from those of an NICU outbreak in 2014 and adult blood cultures. Besides standard infection control measures, the siphons were replaced and weekly decontamination was performed with acetic acid 10%. Seven acquired-resistance genes and 29 virulence-associated genes were detected. Conclusions: It was assumed that both neonates and drains were reservoirs of S. marcescens cross-contamination via the hands of healthcare workers and parents. Initially, standard measures, including hand hygiene, were reinforced. However, definitive containment was achieved only after replacement of the siphons and weekly decontamination with acetic acid. WGS enables faster recognition of an outbreak with accurate mapping of the spread, facilitating the implementation of infection control measures. WGS also provides interesting information about the spread of antibiotic resistance and virulence genes.